Analysis of the Feasibility of Generating Solid Biofuel from Ulex Europaeus Plants (2019)
The Ulex europaeus (also known as Common Gorse) represents a threat to the native ecosystems of different Colombian regions. Recently, the Ministry of the Environment and Sustainable Development introduced protocols for its prevention and management. Even though the Ulex europaeus has a high calorific value, a wide-spread solution for its post-processing is not yet available in its affected areas. In Colombia, the most common method for the disposal of the harvested plant is incineration, given that this is the suggested method by Resolution 684 of 2018. Due to the importance of the problem, this investigation is focused on studying the viability of creating solid biofuel alternatives derived from the plant. Grinded material and briquettes were produced with different log/foliage ratios in order to investigate both the domestic and industrial applications of the plant; e.g. heating, cooking and cogeneration, respectively. A proximate and ultimate analysis was performed on the produced samples. The generated solid biofuel presents 75% of the carbon heat value, a high volatile material content (83.3%), and low ash and Sulphur residues (1.41% and 0.15% respectively). These results applied to both dry and humid samples, demonstrated that the produced solid biofuel is adequate for applications oriented towards heat generation. However, further analysis and process optimization is required in order to establish the generation of solid biofuel as an appropriate use of the Ulex europaeus remnants. By further analyzing the overall process; from plant removal, through residue disposal, and finally remnant conversion, the investigations value chain can be better established and possibly established for real world implementation.